METHODS AND EXPERIENCES OF TEACHING THE ENGLISH LANGUAGE (Journal of Science-Innovative Research in Uzbekistan, 2023)
Currently, disputes about the advantages and disadvantages of foreign and local methods of teaching English are not subside. Criticism Traditional techniques have  become the rule of good tone in modern Russian education. By the standards of  many experts, traditional approaches to learn the language are too boring both in  terms of conducting classes and in content. In this article we will consider the  advantages of TBE (Teachers of Business English) proposed by LTTC (London  Pedagogical College) and materials of the Longman Teacher Development